Fernando Pessoa's unease, or the poetic experience of the boundary (2004)
The following text wants to show that the Book of the Uneasiness, by Fernando Pessoa as Bernardo Soares, is not a mere and extraordinary confession of the vital boredom. What one sets out next, rather, is a reading of Pessoas’s uneasiness as the poetic ex